Paisajes de borde en humedales urbanos: un enfoque de mapeo crítico y análisis normativo en Lima, Perú - Torres Mallma, Sally Fernanda (2025)
The Pantanos de Villa Wildlife Refuge (RVSPV), an urban wetland located in Lima, Peru, is under increasing pressure from urbanization, territorial disconnection, and intensive human activities. This study critically reads the wetland’s edges as strategic territories for ecological connectivity, sustainability, and environmental justice. Using a situated methodology that combines field observation, regulatory analysis, and critical cartography, a typology of edge landscapes was developed, comprising five categories: coastal, road, core, degraded, and built. The analysis identified differentiated socioecological dynamics and prioritized zones according to their vulnerability and management potential. A significant disconnect was found between current public policies and territorial conditions, particularly in degraded and road-adjacent edges, where ecological fragmentation and regulatory neglect configure urban necrospaces. Although legal framework acknowledges edges as buffer zones, it lacks adaptive approaches and differentiated intervention criteria. The study calls for a shift toward restoration and adaptive management strategies grounded in the critical typology developed, reinforcing territorial planning with more integrated regulatory mechanisms sensitive to landscape heterogeneity. This approach is replicable for other fragmented urban wetlands across Latin America.